Analisis Kausalitas Kebijakan Fiskal Ekspansif, Kebijakan Moneter Ekspansif dan Pertumbuhan Ekonomi di Indonesia - Fadhliah Yuniwinsah; Ali Anis (Universitas Negeri Padang, 2020)
This study examined the causality between expansionary fiscal policy, expansionary monetary policy and economic growth in Indonesia’s using a time series data with vector autoregression model (VAR) in the period of 1969-2018. The results of this study showed that are there is no causality between expansionary fiscal policy and expansionary monetary policy but there one-way relationship between them, it is the expansionary monetary policy gives influence to expansionary fiscal policy. There is no causality between expansionary fiscal policy and economic growth but there one-way relationship between them, It is economic growth gives influence to expansionary fiscal policy. And there is no causality between expansionary monetary policy and economic growth but there one-way relationship between them, it is economic growth gives influence to expansionary monetary policy.